2011
DOI: 10.1007/s12541-011-0061-4
|View full text |Cite
|
Sign up to set email alerts
|

A study on optimal design and fatigue life of the common rail pipe

Abstract: To support the latest automobile technology, the next generation of diesel engines is expected to require higher injection pressures than the third generation which can operate at high injection pressures up to 1,800bar. A component in the common rail system, the common rail pipe must have higher strength because it is directly influenced by the high-pressure fuel. Preform design is very important for preventing the head of the common rail pipe from folding in the heading process. In this study, the angle, cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Yigao Ning, et al [1][2] studied the processing and optimization of common rail pipe by means of finite element analysis method and proposed reasonable solutions. Xiang Wang et al [3][4][5] analyzed the design idea and technical scheme of common rail system by combining performance simulation calculation and test verification. Catania et al [6] developed a mathematical model to support experiment, layout and control design as well as performance optimization based on Numerical Simulation of common rail injection system dynamics, and verified the accuracy of the mathematical model on a high-performance test bench.…”
Section: Introductionmentioning
confidence: 99%
“…Yigao Ning, et al [1][2] studied the processing and optimization of common rail pipe by means of finite element analysis method and proposed reasonable solutions. Xiang Wang et al [3][4][5] analyzed the design idea and technical scheme of common rail system by combining performance simulation calculation and test verification. Catania et al [6] developed a mathematical model to support experiment, layout and control design as well as performance optimization based on Numerical Simulation of common rail injection system dynamics, and verified the accuracy of the mathematical model on a high-performance test bench.…”
Section: Introductionmentioning
confidence: 99%
“…In the study described in [5,6], the manufacturing process of the injection pipe head intended for Common Rail systems is analysed in detail. In the first phase of study, it was found that the optimal design of pre-form punch and two-stage heading process significantly contribute to the improvement of fatigue life.…”
Section: Introductionmentioning
confidence: 99%
“…During flange upsetting of tubular parts annular folding is commonly known as a process limit (FIGURE 1a) [2][3][4][5][6][7][8] mainly affected by the unsupported free length of the tubular part leading to buckling behavior during forging. Shafts do often have flanges to feed in or to pass torque or are used as bearing seat requiring sufficient mechanical strength therefore folding is not tolerated leading to a significant weak point of the part.…”
Section: Introductionmentioning
confidence: 99%